The Relationship of Reading Abilities With the Underlying Cognitive Skills of Math: A Dimensional Approach - Bernabini, Luca; Bonifacci, Paola; de Jong, Peter F. (Frontiers in Psychology, 2021)
Math and reading are related and math problems are often accompanied by problems in reading. In the present study we used a dimensional approach and we aimed to assess the relationship of reading and math with the cognitive skills assumed to underlie the development of math. The sample included 97 children from 4th and 5th grades of primary school. Children were administered measures of reading and math, nonverbal IQ and various underlying cognitive abilities of math (counting, number sense, and number system knowledge). We also included measures of phonological awareness and working memory (WM). Two approaches were undertaken to elucidate the relations of the cognitive skills with math and reading. In the first, we examined the unique contributions of math and reading ability, as well as their interaction, to each cognitive ability. In the second, the cognitive abilities were taken to predict math and reading. Results from the first set of analyses showed specific effects of math on number sense and number system knowledge, whereas counting was affected by both math and reading. No math by reading interactions were observed. In contrast, for phonological awareness, an interaction of math and reading was found. Lower performing children on both Math and Reading performed disproportionately lower. Results with respect to the second approach confirmed the specific relation of counting, number sense and number system knowledge to math, and the relation of counting to reading, but added that each math related marker contributed independently to math. Following this approach, no unique effects of phonological awareness on math and reading were found. In all, the results show that math is specifically related to counting, number sense, number system knowledge. The results also highlight what each approach can contribute to an understanding of the relations of the various cognitive correlates with reading and math.